A randomized trial comparing laryngeal mask airway to endotracheal tube in children undergoing upper gastrointestinal endoscopy - Fuentes-Garcìa, V.E.; Morales-Pérez, E.; Ramìrez-Mora, et al., J.C. (Acta Biomedica Atenei Parmensis, 2006)
Although the efficacy of laryngeal mask airway (LMA) has been demonstrated for securing patency of the airway in children, it has not yet been compared to endotracheal tube (ET) in this population. This study aimed to compare the safety and efficacy of LMA vs. ET in children undergoing elective diagnostic upper gastrointestinal endoscopies. Sixty ASA I-III patients were randomly allocated to ET (Group I) or LMA (Group II). A set of cardiovascular and respiratory parameters were obtained before, during and after the endoscopic procedure. The recovery time and the time to discharge were also registered. The cardiovascular and respiratory parameters evaluated in the study varied across the different evaluation periods. However, they remained within physiological ranges and were not different between groups. The median (range) recovery time was 4 (2-10) min and the time to discharge was 58 (36-88) min in the ET group and 3 (1-7) min and 50 (35-67) min in the LMA group (P > 0.10), respectively. In a 16 month-old, 80 cm and 10 kg girl, we failed to secure the patency of the airway with LMA. In conclusion, the LMA was as effective and safe as ET for securing the airway of children undergoing diagnostic upper endoscopies. However, the 3% failure rate occurred with LMA.